Natural enemies of Coelomera lanio (Coleoptera: Chrysomelidae) in the region of Viscosa, Minas Gerais, Brazil - Silveira, R.D.=700 1 Dos Anjos, N.
(Es, En)
ilus., 28 ref.
Keywords: COLEOPTERA; CONTROL BIOLOGICO; PLAGAS DE PLANTAS; INSECTOS DEPREDADORES DE LAS HOJAS; ENEMIGOS NATURALES; CECROPIA; ARBOLES MADERABLES; COSTA RICA; COELOMENA LANIO